Voting Behavior of Women's in Char Areas: Examining Challenges and Patterns of Women's Voting Behavior in Char Areas (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The central feature of liberal democratic government is representation between men andwomen in political activity. Both men and women must have an equal opportunity to engage equally in allrespects and in all stages of democratic systems in accordance with international norms. While in manycountries women have taken great strides in securing a vote and the right to be elected to politicalpositions, they make up less than 11. While different legislative enactments and commissions forsupporting gender equality have been created, gender differences continue to occur, particularly in thepolitical arena. Encouraging women in politics is one of female empowerment's key fields. Theparticipation of women at the policy level not only improves their social, political and economic status,but also reinforces public structures by enhancing their inclusiveness and purpose. While women havemade greater progress, because of political, socioeconomic, ideological and psychological factors theystill cannot engage in politics. Women's fair representation in this framework must also be analyzed inthe proper way in order to provide good democratic governance. There will be no true democracy if weneglect or put aside the voices and problems of women that make up half of the country's population.This paper analyses women's difficulties, voting behavior and problems in national and localgovernment.